Communication engineering - Everitt, William Littell (McGraw-Hill, 1956)
Chapter 1. Fundamental principles of communication networks, Chapter 2. Methods of network - behavior analysis, Chapter 3. Steady - state analysis and network theorems, Chapter 4. Resonance,...